(3HOGFY GdaQGFOs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s ((3eMeO Hf SGde GdJMQjQi s)
(3ChdgG (B:s
(3gPg ahGFO eNJdaI GdCfhGY aGFOI Mbhb GdeGdc TF hMbhb Gdedc TF aMbhb GdeGdc JLH def dg Ydi CNjg Mb s
(3BNQgG (B:s
(3aGFOI ai GdHOd JfJgi Hbhd GdTGYQ adG hCHjc NjQ efc Efi djDPfi GdJMee hGdUgjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs